A statistical approach to estimate wind speed distribution in ibadan, nigeria (2016)
In this paper, the wind energy potential in Ibadan is statistically analyzed using daily wind speed data for 10 years (1995-2004) obtained from the International Institute of Tropical Agriculture (IITA) and 1 year (2006) obtained from Nigeria Micro-scale Experimental (NIMEX) Ibadan,Nigeria. The statistical wind data set was analyzed using Weibull distributions in order to investigate the Weibull shape and scale parameters. The daily, monthly, seasonal, and yearly wind speed probability density distributions were modeled using Weibull Distribution Function. The measured annual mean wind speed was found to be 0.76 m/s and the total extractable wind power has been estimated as 0.33 kW at IITA while the annual mean wind speed ranged between 0.74 m/s, 1.02 m/s, 1.16 m/s and 1.34 m/s at (3 m, 6 m, 12 m and 15 m) respectively at NIMEX. The maximum extractable annual wind power density value of 0.90W /m2 for the whole year at IITA and 5.61W / m2 at the highest height of 15 m at NIMEX indicated that, Ibadan can be classified as a low wind energy region and it belongs to the wind power class 1, since the density is less than 100W /m2 . It is concluded that at both sites, the highest wind speed that prevailed in Ibadan is March and the location can be explored for wind power.